Eco-friendly corrosion mitigation of AISI 1020 steel in alkaline media using Arachis hypogaea shell extract: concentration and immersion time effects - Md Ali, Masalina; Alias, Siti Khadijah; Hisham, Munzir Izhar; Nik Pa, Nik Masmiati; Tumin, Najwa Delaila; Pahroraji, Hazriel Faizal; Mat Shah, Muhammad Amir; Abdullah, Bulan (UiTM Press, 2026)
Corrosion is a major factor limiting the service life of carbon steel, particularly in alkaline environments encountered in industries such as oil and gas. The objective of this study is to evaluate Arachis hypogaea (groundnut) shell extract as a sustainable corrosion inhibitor for AISI 1020 steel in alkaline media. The inhibitor was prepared via Soxhlet extraction and rotary evaporation and characterized using Fourier Transform Infrared (FTIR) spectroscopy. Corrosion performance was assessed using weight loss measurements, macrostructural and microstructural observations, and Rockwell hardness testing. Experiments were conducted at inhibitor concentrations of 10%, 20%, and 30% v/v, with immersion periods of 7, 14, and 21 days. Results revealed a clear correlation between inhibitor concentration, immersion time, and corrosion resistance. Increasing the inhibitor concentration markedly reduced the corrosion rate, achieving a maximum inhibition efficiency of 97.331% at 30% after 7 days. Prolonged immersion maintained superior protection compared to uninhibited control, indicating sustained inhibitor activity. Additionally, samples immersed with the presence of Arachis hypogea shell extract revealed improved hardness values, suggesting enhanced mechanical performance alongside corrosion resistance. The findings confirm the potential of Arachis hypogaea shell extract as an eco-friendly, cost-effective corrosion mitigation approach for carbon steel in alkaline environments, offering benefits in both protection and mechanical durability.